The psychosocial impact of human papillomavirus testing in primary cervical screening— a study within a randomized trial. Issue 4 (1st July 2008) - Kitchener, H. C.; Fletcher, I.; Roberts, C.; Wheeler, P.; Almonte, M.; Maguire, P.
Abstract : The purpose of the study was to assess the psychosocial impact of human papillomavirus (HPV) testing as an adjunct to cytology in routine primary cervical screening. A controlled study of the psychosocial impact of HPV testing within a randomized trial of HPV testing to assess its efficacy in cervical screening was carried out. The trial provides a randomized setting of revealed HPV results versus concealed results permitting valid comparisons for assessing true psychosocial impact. The setting comprised a large number of general practices in primary care. Women aged 20–64 years who underwent routine cervical screening participated in the study. The intervention was a revealed high-risk HPV test result in addition to cervical cytology. The main outcome was measured using General Health Questionnaire (GHQ-28), Spielberger State–Trait Anxiety Inventory, and Sexual Rating Scale (SRS). Among women with either mildly abnormal or normal cytology, receiving an HPV(+ ve) result did not impact significantly on GHQ caseness and mean scores or on Spielberger State and Trait scores when compared with women in whom the HPV(+ ve) test result was concealed. Among women with normal cytology, receiving an HPV(+ ve) result was associated with a reduction in the Sexual Rating Scale compared with similar women whose HPV(+ ve) result was concealed. HPV testing does not add significant psychologic distress when combined with cytology in routine primary cervical screening.